Evaluating tofacitinib citrate in the treatment of moderate-to-severe active ulcerative colitis: design, development and positioning of therapy - Tran, Vivy (Clin Exp Gastroenterol, 2019)
The etiology of ulcerative colitis (UC) is complex and involves a host of genetic, epigenetic and environmental factors. Over the last thirty years, signaling pathways like the Janus kinase (JAK) signaling pathway have been implicated in its pathogenesis. Pharmacologic blockade of this pathway is available through several small molecule inhibitors, including tofacitinib. Tofacitinib is an orally administered pan-JAK inhibitor that was first approved by the Food and Drug Administration (FDA) for use in rheumatologic disorders such as rheumatoid arthritis and psoriatic arthritis. The FDA approved its use in moderate-to-severe active ulcerative colitis in 2018. The aim of this review will be to discuss the role of tofacitinib in ulcerative colitis. We will discuss the role of JAK-STAT signaling, clinical data available for tofacitinib, and the safety profile for this therapy. Tofacitinib’s place in the UC management algorithm is currently being debated. This effective oral therapy is poised to be a mainstay of UC therapeutics. This review will highlight the key clinical features and detail the UC experience to date.